POLA PERJALANAN WISATA BAHARI KABUPATEN BINTAN - Susanto, Dedi; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Bintan has great natural tourism potential, especially marine tourism. Therefore, it is necessary to have a arranged and planned travel pattern to increase visitors in Bintan. This study was conducted to reveal the potential of marine tourism that is not yet known by tourists. This study aims to identify the object and potential of marine tourism and reveal the cluster of travel patterns, and recommend the travel pattern of marine tourim in Bintan. This study used descriptive qualitative method. The data collection techniques in this study using literature study, observation, interviews, and documentation. The results of this study reveal the object and potential of marine tourism in Bintan, and recommend the travel pattern of marine tourism in Bintan District. Keywords : travel patterns, marine tourism, district Bintan.